Densification kinetics and mechanical properties of tantalum carbide. (June 2018) - Nisar, Ambreen; Ariharan, S.; Balani, Kantesh
Abstract: Sintering kinetics and densification of tantalum carbide (TaC) based ultra-high temperature ceramics (UHTC) processed using spark plasma sintering (SPS) were investigated. Samples sintered in the temperature ranging from 1600 °C to 2300 °C for 15 min under uniaxial pressure of 50 MPa showed increasing densification (~77% to 99% from 1600 °C to 2300 °C) accompanied by substantial grain growth (~0.57 μm to ~4.05 μm). Below 1900 °C, the densification mechanism was grain-boundary sliding with an apparent activation energy of 97.3 ± 10.2 kJ/mol. However above 1900 °C, the activation energy was found to be 232.7 ± 19.6 kJ/mol with grain boundary diffusion to be an active densification mechanism. The flexural strength (from 161.3 ± 10.4 MPa to 326.5 ± 10.5 MPa) and elastic modulus (from 375.7 ± 3.1 GPa 535.4 ± 4.7 GPa) was observed to increase with the increasing sintering temperature. The study explicitly establishes that the dense bulk TaC ceramic can be produced by SPS in a shorter time and lower sintering temperature, while maintaining the compositional stoichiometry. Graphical abstract: Highlights: Effect of spark plasma sintering (SPS) on the densification and microstructure of an ultra-high temperature ceramic, TaC Creep model to study the densification mechanism of TaC Grain growth model was applied to identify the grain growth mechanisms. Activation energy for densification of TaC has been evaluated. Correlating sintering kinetics with the microstructural and mechanical properties of TaC